PEMETAAN TINGKAT KERAWANAN TSUNAMI DI PANTAI PARANGTRITIS DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFI - Qoriadi, M. Taufan; Subardjo, Petrus; Helmi, Muhammad (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Tsunami is one of the natural events that can not be predicted. The causal of tsunami can be submarine earthquake, submarine volcanic eruptions, or submarine landslide. The mapping of tsunami vulnerability in Parangtritis Beach is an effort of disaster mitigation to minimize the negative impact of tsunami. The research is aimed to map the vulnerability of tsunami disaster in the area of Parangtritis Beach. There are five classes of vulnerability level i.e. very vulnerable class, vulnerable class, slightly vulnerable class, safe class, andvery safe class. The places in Kretek Sub-district which are rated vulnerable (very vulnerable, vulnerable, and slighty vulnerable) is covering the area of 1.334,22 hm2 or 52,93 % of Kretek Sub-district. The places in Kretek Subdistrict which are rated safe is covering the area of 1.186,27 hm2 or 47,06% of Kretek Subdistrict.